2017
DOI: 10.1038/nature21049
|View full text |Cite
|
Sign up to set email alerts
|

Communication between viruses guides lysis–lysogeny decisions

Abstract: Temperate viruses can become dormant in their host cells, a process called lysogeny. In every infection, such viruses need to decide between the lytic and the lysogenic cycles, i.e., whether to replicate and lyse their host or to lysogenize and keep the host viable. Here we show that viruses (phages) of the spBeta group use a small-molecule communication system to coordinate lysis-lysogeny decisions. During infection of its Bacillus host cell, the phage produces a 6aa communication peptide that is released to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
540
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 504 publications
(559 citation statements)
references
References 36 publications
(41 reference statements)
15
540
0
4
Order By: Relevance
“…2009, Erez et al. 2017). Increases in FIC relative to the controls coincided with increases in VP (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009, Erez et al. 2017). Increases in FIC relative to the controls coincided with increases in VP (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…2009, Erez et al. 2017). Also, the level of lysogeny in viral communities at the surface may be influenced by environmental parameters such as temperature, trophic conditions, or drastic changes in salinity (e.g., Williamson and Paul 2004, 2006, Cissoko et al.…”
Section: Introductionmentioning
confidence: 99%
“…Key among these are the insertion/excision events. The benefits of lysogeny versus lysis are likely to depend on the prevailing environmental conditions, for example, prophage insertion is more likely when the multiplicity of infection is high [62] (when the availability of hosts is limited), whereas excision is induced by the bacterial SOS response [63] (when the probability of vertical transmission in that host is low).…”
Section: Future Directions -Unraveling the Evolutionary Ecology Of Tementioning
confidence: 99%
“…In a recent paper published in Nature, the sensational claim was made that phage particles of the SPbeta group are able to communicate with each other by allegedly producing an hexapeptide that is released in the culture medium [3]. Progeny phages were said to be able to measure the concentration of this peptide and if the concentration was sufficiently high, the phages would decide to lysogenize their bacterial host cells instead of killing them by lysis.…”
mentioning
confidence: 99%
“…The original aim of the Erez et al study [3] was to investigate whether Bacillus subtilis bacteria infected with the phi3T phage were able to secrete peptides that would alert other B subtilis cells to the impending likelihood of phage infection, which would allow these cells to choose the lysogenic option and avoid the deadly lytic cycle. When it was found that the infected bacteria did produce a signalling hexapeptide, the authors ascribed its synthesis to the infecting phage, assuming that viruses synthesize peptides in order to communicate with other virus particles !…”
mentioning
confidence: 99%